Novel variants in the PRDX6 Gene and the risk of Acute Lung Injury following major trauma - Localio A Russell; Bellamy Scarlett; Gallop Robert; Lanken Paul N; Feng Rui; Li Mingyao; Meyer Nuala; Aplenc Richard; Rushefski Melanie; Feinstein Sheldon I; Fisher Aron B; Albelda Steven M; et al. (BMC, 2011)
Abstract Background Peroxiredoxin 6 (PRDX6) is involved in redox regulation of the cell and is thought to be protective against oxidant injury. Little is known about genetic variation within the PRDX6 gene and its association with acute lung injury (ALI). In this study we sequenced the PRDX6 gene to uncover common variants, and tested association with ALI following major trauma. Methods To examine the extent of variation in the PRDX6 gene, we performed direct sequencing of the 5' UTR, exons, introns and the 3' UTR in 25 African American cases and controls and 23 European American cases and controls (selected from a cohort study of major trauma), which uncovered 80 SNPs. In silico modeling was performed using Patrocles and Transcriptional Element Search System (TESS). Thirty seven novel and tagging SNPs were tested for association with ALI compared with ICU at-risk controls who did not develop ALI in a cohort study of 259 African American and 254 European American subjects that had been admitted to the ICU with major trauma. Results Resequencing of critically ill subjects demonstrated 43 novel SNPs not previously reported. Coding regions demonstrated no detectable variation, indicating conservation of the protein. Block haplotype analyses reveal that recombination rates within the gene seem low in both Caucasians and African Americans. Several novel SNPs appeared to have the potential for functional consequence using in silico modeling. Chi2 analysis of ALI incidence and genotype showed no significant association between the SNPs in this study and ALI. Haplotype analysis did not reveal any association beyond single SNP analyses. Conclusions This study revealed novel SNPs within the PRDX6 gene and its 5' and 3' flanking regions via direct sequencing. There was no association found between these SNPs and ALI, possibly due to a low sample size, which was limited to detection of relative risks of 1.93 and above. Future studies may focus on the role of PRDX6 genetic variation in other diseases, where oxidative stress is suspected.